Rigid–flexible coupled dynamic response of steel–concrete bridges on expressways considering vehicle–road–bridge interaction. Issue 1 (January 2020) - Chen, Enli; Zhang, Xia; Wang, Gaolei
Steel–concrete bridges on highways are now widely used, and their dynamic coupling effect is more prominent under heavy vehicles. At present, for the study of vehicle–bridge coupling, it is difficult to reflect the mechanical response characteristics of the bridge pavement because the bridge pavement (road) is often considered as a load. In order to get closer to reality, we use the whole vehicle model and the bridge model to realize the dynamic coupling of highway vehicle–bridge. Moreover, the vehicle model can take into account tire characteristics, such as various linear and nonlinear suspension characteristics, and tire–ground contact characteristics. So, a new vehicle–road–bridge interaction method with higher computational efficiency is proposed. This method can be used not only to analyze the overall mechanical response of bridge structure such as deflection and stress but also to analyze the dynamic characteristics of driving vehicles and the coupling force between tires and pavement and then to analyze the dynamic deformation and stress of asphalt pavement layers on the bridge. First, according to the construction drawings of a steel–concrete bridge on a highway and a Dongfeng brand three-axle vehicle, a vehicle–road–bridge interaction rigid–flexible coupling model was established. Second, the correctness and effectiveness of the vehicle–road–bridge interaction model were verified by field testing. Finally, the dynamic response of the vehicle–road–bridge interaction rigid–flexible coupling model was analyzed.